Large Corporate Organizations in Mexico and Chile; an Analysis of Profiles with Respect to Their Communications on Social Responsibility - Wendlandt Amezaga, Teodoro R.; Valdés Cuervo, Angel A.; Carlos Martínez, Ernesto A.; Ochoa Silva, Beatriz (Cuadernos de Administración, 2015)
This study identified subgroups of companies based on their communications on social responsibility (CSR) and established differences among these related to their country of origin, origin of the capital, extension in their communications, and industrial activity. In non-probabilistic manner, 300 large companies were selected from Mexico and Chile. Through non-hierarchical k-means conglomerate test, two subgroups of companies were identified according to their CSR frequencies (motivational principles [F = 217.1, p < .000], management processes [F = 990.4, p < .000], and interest groups [F = 1317.3, p < .000]). The first conglomerate integrated by 100 companies (33%) was denominated low profile of communications on social responsibility (LP-CSR) and the second, which included 200 companies (67%), was denominated high profile of communications on social responsibility (HP-CSR). In the HP-CSR subgroup there is a higher proportion of companies of Mexican origin (X2 = 38.50, p<.000), of foreign capital (X2=53.40, p<.000), with medium extension levels (X2=4.76, p=.029) or extensive (X2=143.15, p<.000), with industrial activities, of consumer goods (X2=10.12, p=.001), chemical (X2=16.13, p < .000), natural resources (X2=13.50, p<.000), and construction materials (X2=6.54, p=.011).